Amino Acid Sensing via General Control Nonderepressible-2 Kinase and Immunological Programming - Battu, Srikanth; Minhas, Gillipsie; Mishra, Aman; Khan, Nooruddin (Frontiers in Immunology, 2017)
Metabolic adaptation to the changing nutrient levels in the cellular microenvironment plays a decisive role in the maintenance of homeostasis. Eukaryotic cells are equipped with nutrient sensors, which sense the fluctuating nutrients levels and accordingly program the cellular machinery to mount an appropriate response. Nutrients including amino acids play a vital role in maintaining cellular homeostasis. Therefore, over the evolution, different species have developed diverse mechanisms to detect amino acids abundance or scarcity. Immune responses have been known to be closely associated with the cellular metabolism especially amino acid sensing pathway, which influences innate as well as adaptive immune-effector functions. Thus, exploring the cross-talk between amino acid sensing mechanisms and immune responses in disease as well as in normal physiological conditions might open up avenues to explore how this association can be exploited to tailor immunological functions towards the design of better therapeutics for controlling metabolic diseases. In this review, we discuss the advances in the knowledge of various amino acid sensing pathways including general control nonderepressible-2 kinase (GCN2) in the control of inflammation and metabolic diseases.